2016
DOI: 10.1038/srep33606
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hypothalamic MCT1 expression increases food intake and alters orexigenic and anorexigenic neuropeptide expression

Abstract: Hypothalamic glucosensing, which involves the detection of glucose concentration changes by brain cells and subsequent release of orexigenic or anorexigenic neuropeptides, is a crucial process that regulates feeding behavior. Arcuate nucleus (AN) neurons are classically thought to be responsible for hypothalamic glucosensing through a direct sensing mechanism; however, recent data has shown a metabolic interaction between tanycytes and AN neurons through lactate that may also be contributing to this process. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 61 publications
7
77
1
1
Order By: Relevance
“…Unfortunately, we were not able to evaluate intracellular GLUT2 expression by immunohistochemistry; therefore, it is not known whether possible changes in GLUT2 localization mediated by the transduction contributed to the loss of function. Our present results and previous findings (Elizondo‐Vega et al, 2016) indicate that injection of the adenovirus in the basal 3V results in preferential transduction in ependymal cells and tanycytes but not in neurons or astrocytes. Nevertheless, other authors have reported that serotype 5 adenoviruses exhibit a glial tropism (Cazzin et al, 2010; Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Unfortunately, we were not able to evaluate intracellular GLUT2 expression by immunohistochemistry; therefore, it is not known whether possible changes in GLUT2 localization mediated by the transduction contributed to the loss of function. Our present results and previous findings (Elizondo‐Vega et al, 2016) indicate that injection of the adenovirus in the basal 3V results in preferential transduction in ependymal cells and tanycytes but not in neurons or astrocytes. Nevertheless, other authors have reported that serotype 5 adenoviruses exhibit a glial tropism (Cazzin et al, 2010; Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…We have previously shown that 3V injection of an adenovirus with the same capsid transduces mainly tanycytes (Elizondo‐Vega et al, 2016). To corroborate that this also occurs with Ad‐shGLUT2, we used spectral confocal microscopy to evaluate EGFP expression (green), the tanycyte marker, anti‐vimentin (red), and the adult neuronal marker, NeuN (magenta) (Figure 2a–l).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypothalamus, the arcuate nucleus (AN) is composed of clustered neuronal populations that inhibit or initiate food intake through the release of anorexigenic or orexigenic peptides, respectively (Schwartz et al, 2000). There is great interest in understanding the precise molecular and cellular mechanisms that control glucosensing, especially given that diabetes and obesity may be induced by a dysregulation in this process (Elizondo-Vega et al, 2016). …”
Section: Hypothalamus and Energy Balancementioning
confidence: 99%
“…They also express the molecular machinery that permits glucose sensing (García et al, 2003; Cortés-Campos et al, 2011; Orellana et al, 2012) and transmit signals to AN neurons (Elizondo-Vega et al, 2016). Due to their privileged position in the hypothalamus, tanycytes can also detect mitogenic and neurodifferentiating signals present in the peripheral blood or in the CSF (Robins et al, 2013; Chaker et al, 2016).…”
Section: Hypothalamus and Energy Balancementioning
confidence: 99%